A representação social da moradia por idosos: um estudo sobre a autoconstrução na baixada de Belém - NOBRE, Priscila Gleyce Nunes (Universidade Federal do Pará, 2014)
The research marks the 1970s, because this period together with the previous two decades (1950s and 1960s ), consolidated two crucial phenomena for setting social, economic and Brazilian space: the intense urbanization process experienced by Brazil with the consequent consolidation of the developmental standard proposed by the federal government. Because of these factors, the lowlands were a viable option for workers who sought to secure housing in Belém do Pará, driven by the desire for better living conditions. Have, as a reference point, the self-built housing made by seniors. Focuses on the social representation of this action for 8 subjects, now elderly, working-class neighborhood of the lowland Guama in Belém do Pará, more specifically, the Pedreirinha Passage that protects the elderly migrants between its residents and remain there since that time. Initially a survey was applied in all the houses on the street to select those that were within the scope of the search. 48 homes were visited with subjects respondents. Of these, 18 were selected elderly where they resided. Thus, the houses were chosen, in which the resident interviewed in the survey reported that the house was proper and that the construction took place over the 70, the elderly resident today. Finally, interviews were held to 8 selected subjects, using as instrument for data acquisition in the form with the intention of achieving direct information of the respondents. Notes that the resistance based on actions arising out of individuals before the emergency needs without political or ideological direction set can sometimes compared to traditional forms of struggle and resistance, seem isolated attitude and dead for system changes.